OPTIMASI PENJADWALAN JUMLAH PERAWAT DENGAN MENGGUNAKAN LINEAR PROGRAMMING - Mustika Widyaningsih (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2018)
This study aims to determine the optimization of the scheduling decision of the number of nurses at the PKU Muhammadiyah Surakarta Hospital using linear programming. The preparation of the schedule for the number of nurses assigned to this method can optimize the performance of nurses and reduce the costs incurred by the hospital for nurses' salaries by minimizing the objective function, namely the need for efficient nurses per shift. In this study the variables used are the decision variables for the number of nurses on duty. Decision variables are used to formulate objective functions and mathematical constraint functions.This research is a research with secondary data source. The data in the research was obtained by collecting administrative data at RS PKU Muhammadiyah Surakarta. The data used are data on the number of IGD patients and attendance data of IGD nurses in April 2018. Data analysis techniques used are linear programming using excel solver and SPSS.Based on the result of the solver, the morning shift requires at least 8 nurses, the day shift requires 8 nurses, and the night shift requires 12 nurses. While based on result of anova test, the value of significance (Sig.) Is 0,829> 0,05, so it can be concluded that statistically the average number of nurses from the three shifts is the same or no difference significantly if the hospital use 12 or 8 person nurse . However, when viewed from the operational point of view the difference of four people is certainly different because it will cause different costs. Keywords : Optimization, Scheduling, Linear Program, Integer.